Pengaruh Profitabilitas, Transfer Pricing dan Likuiditas Terhadap Tax Avoidance - Ganang Prasetyo, Mohammad; Arieftiara, D.; Sumilir, (Jurnal Akunida, 2022)
This study aims to analyze the influence of profitability, transfer pricing, and liquidity on tax avoidance in companies in the manufacturing sector listed on the Indonesia Stock Exchange (BEI) in 2017-2019. The data analysis technique is panel data regression analysis using STATA Ver. 16. The population in this study is companies in the manufacturing sector listed on the IDX. The sampling technique used was purposive sampling and produced 31 samples with the study period in 2017-2019 so there were 93 sample units. The results showed that profitability has a negative effect on tax avoidance, transfer pricing has no effect on tax avoidance, and liquidity have a negative effect on tax avoidance. The results of this study imply that transfer pricing in the companies included in this research sample is not used as a manager's motive to regulate the tax burden that must be paid, but really as a strategy to obtain optimum/beneficial costs for the company, however managers must pay attention to the principle of fairness in the value of transactions with affiliated parties, especially overseas companies, because this is still under the spotlight of the tax authorities as a means of tax avoidance.